The Policy of Legal-Entity State Higher Education Institutions (PTN-BH) Determination Viewed from Material Law Institutions - Isra Nurhanifah; Eny Kusdarini (Program Pasca Sarjana Unej, 2022)
PTN-BH is a state university established by government with the status as an autonomous public legal entity. The existence of PTN-BH in ensuring quality and affordable education is questionable because the application of the non-profit principle in the autonomy of higher education is the basis that students must be protected in the imposition of education costs that the state cannot afford, especially in universities with legal entity status. The purpose of this study is to determine the urgency of PTN-BH determination in terms of material law. This study uses a normative juridical method, the data sources used are secondary data and primary data analyzed qualitatively. The results of the study indicate the emergence of the term Legal Entity State Higher Education Institutions beginning with the enactment of Law Number 9 of 2009 concerning Educational Legal Entities, named PTN-BHMN. In the end, the BHP Law was annulled by the Constitutional Court, with the Constitutional Court Decision Number 11-14-21-126-136/PUU-VII-2009 dated March 10, 2010. The BHP Law was declared contrary to the 1945 Constitution of the Republic of Indonesia that leads to no legally binding power. The enactment of Law Number 12 of 2012 concerning Higher Education becomes the basic foundation for State Universities Ex-BHMN to switch status to PTN-BH. With full autonomy, a state university can independently manage its own household according to the purpose of the campus. It is hoped that universities can develop and innovate more quickly. State universities with the status of Legal Entities actually have wider autonomy which means that PTN-BH can take care of their household more independently. For example, a higher level education institution with the status of a PTN-BH can open a new study program or close it when it is deemed no longer needed. Likewise in financial matters, personnel affairs are also regulated by its higher level education institution.